1992
DOI: 10.1128/iai.60.1.1-7.1992
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis carinii induces an oxidative burst in alveolar macrophages

Abstract: There is evidence that alveolar macrophages (AM) play a role in the clearing of Pneumocystis carinii from the lungs. To investigate the mechanisms involved in this process, we studied in vitro the induction of an oxidative burst by P. carinii in a cell line of macrophages (NR8383) and AM from normal rats. P. carinui was added to macrophage monolayers (106 cells), and the H202 produced after 4 h of incubation was measured. Both NR8383 macrophages and normal rat AM produced H202 in response to P. carinii cysts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 24 publications
(21 reference statements)
3
17
0
Order By: Relevance
“…and through an increased potential of supcroxidc production, since the PMA response was also increased in IFN--,treated cells. The ability of macrophages to activate the respiratory burst when challenged with pneumocysts is in agreement with the findings of Hidalgo et ai [6] and Taylor ct al. [5], who used a macrophage cell line and alveolar macrophages from rats and rat serum for opsonization.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…and through an increased potential of supcroxidc production, since the PMA response was also increased in IFN--,treated cells. The ability of macrophages to activate the respiratory burst when challenged with pneumocysts is in agreement with the findings of Hidalgo et ai [6] and Taylor ct al. [5], who used a macrophage cell line and alveolar macrophages from rats and rat serum for opsonization.…”
Section: Discussionsupporting
confidence: 91%
“…is known to be important for the ability of phagocytic cells to kill ingested microorganisms. Previous studies, using chemoluminescence or peroxidase assay for HiO; determination, showed that pneumocysts were able to activate the respiratory burst in rat macrophages and a macrophage cell line [5,6]. We have studied the ability of human monocytes and monocyte-derived maerophages to produee Oi , when stimulated with P. carinii.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, previous studies have reported a role for both reactive oxygen species in the killing of P. carinii. Some reports have shown that both hydrogen peroxide and superoxide are directly toxic to P. carinii (12)(13)(14). Furthermore, studies have shown that P. carinii can elicit an oxidative burst of both hydrogen peroxide and superoxide from macrophages (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…II.-1 elicits local accumulation and activation of inflammatory cells (8,11,21). These cells are considered important in host defenses against P. carinii (3,4,6,(22)(23)(24)(25)(26) and, indeed, reconstitution of P. carinii-infected SCID mice with immunocompetent spleen cells induces significant recruitment of inflammatory cells into bronchoalveolar lumina (3,5). The effect of 35F5 treatment on pulmonary inflammation in reconstituted SCID mice was therefore investigated.…”
Section: Kinetics Of Ll1 Production In Reconstituted Scid Micementioning
confidence: 99%